Personal history of voluntary HIV counseling and testing (VCT) among adults aged 19-35 years living in peri-urban communities, Chiang Mai, northern Thailand - Surinda Kawichai (2018)
This study investigates the self-reported history of HIV voluntary counseling and testing (VCT) among adults, aged 19-35 years, in northern Thailand. Participants were interviewed about their HIV testing history and risk behavior. Overall, 47% of 2251 participants had previously been tested, of whom 64% were tested at government clinics. Of those tested at private clinics, 50% reported not receiving pre- and post-test counseling, compared to 15% of those tested in government clinics. Ten percent of those tested had not received their test results. Among those who had never been previously tested for HIV, 66% believed they were not at risk, although 1.5% (2.7% among men) were HIV infected. Although VCT is widely available and utilized by the population of northern Thailand, substantial numbers of HIV infected persons have not been tested for HIV and among those tested many have not received comprehensive counseling. A Thai government policy enforcing effective counseling to accompany HIV testing is urgently needed. © 2005 Springer Science+Business Media, Inc.